Study of the coefficient of friction and forward slip in cold rolling of stainless steel AISI 430 in Sendzimir mills - André C.M. Miranda; Carlos L. Neto; Wilian da S. Labiapari; Pedro Henrique R. Pereira; Paulo R. Cetlin; Ariel R. Arias (Journal of Materials Research and Technology)
For most AISI 430 stainless steel applications, aesthetic appeal is mandatory. To avoid the generation of scratches on the strip surface during cold rolling on a Sendzimir mill, forward and backward slip are required to synchronize the speed of the driven deflector rolls. Forward slip is also an important variable to predict skidding and an investigation of forward slip behavior is proposed in this paper. A comparison of analytical and numerical models of the rolling friction hill is presented to determine the most suitable one to investigate friction and forward slip in the cold rolling of the AISI 430 produced at Aperam. In addition, the finite element method is employed in the computational simulations using an Abaqus implicit model. The AISI 430 flow curve used in the analysis is obtained by two different methods, and the evolution of the strip surface during rolling is analyzed. To investigate the typical coefficient of friction of the cold rolling process, data from 60 industrial coils is implemented in the analytical model to statistically validate the results. The study has performed a comparison of analytical and numerical models of the friction hill, indicated a suitable model based on industrial data, and identified the typical coefficient of friction in the cold rolling of AISI 430 in a Sendzimir mill. The findings of this work will allow the improvement of forward slip prediction for industrial purposes, and will contribute to further investigation of forward slip influence on the surface quality of AISI 430 cold rolled strip.